Analisis kunjungan ulang wisatawan ke daya tarik wisata tanah lot di era new normal - A.A.A Ribeka Martha Purwahita (Forum Manajemen, 2023)
Tanah Lot tourist attraction is a popular tourist attraction among local and foreign tourists. Especially in the new normal era, Tanah Lot is preparing to be reopened as a major tourist destination for tourists visiting the island of Bali. This study develops a model with several hypotheses regarding tourist visits to the Tanah Lot tourist attraction. The method used is the PLS-SEM method. Structural model analysis or inner model is carried out to determine the relationship between latent variables that influence (exogenous) and latent variables that are affected (endogenous). This study uses 100 respondents, who are tourists visiting Tanah Lot. There are five latent variables, namely the quality of tourist objects, the attractiveness of tourist objects, visiting experience, tourist satisfaction and interest in visiting. The five latent variables are measured by a Likert scale. The description of this variable is an illustration to find out and increase the tourist attraction of Tanah Lot.